Determinación de polimorfismos en los genes de los miR-494, miR-155, miR-144 miR-17, miR-663, miR-4505 y su correlación con trastorno de ansiedad generalizada en una muestra de Bogotá, Colombia (2022)
The aim of this work was to determine if there is an association between a single nucleotide polymorphism of the genes of miR-494, miR-155, miR-144-3p and miR-17, miR663 and miR-4505, with the diagnosis of generalized anxiety disorder (GAD) in a sample of participants from Bogotá, Colombia